Next-generation humanized NSG-SGM3 mice are highly susceptible to Staphylococcus aureus infection - Sophia Hung; Sophia Hung; Sophia Hung; Amelie Kasperkowitz; Florian Kurz; Liane Dreher; Joachim Diessner; Eslam S. Ibrahim; Eslam S. Ibrahim; Stefan Schwarz; Stefan Schwarz; Knut Ohlsen; et al. (Frontiers in Immunology, 2023)
Humanized hemato-lymphoid system mice, or humanized mice, emerged in recent years as a promising model to study the course of infection of human-adapted or human-specific pathogens. Though Staphylococcus aureus infects and colonizes a variety of species, it has nonetheless become one of the most successful human pathogens of our time with a wide armory of human-adapted virulence factors. Humanized mice showed increased vulnerability to S. aureus compared to wild type mice in a variety of clinically relevant disease models. Most of these studies employed humanized NSG (NOD-scid IL2Rgnull) mice which are widely used in the scientific community, but show poor human myeloid cell reconstitution. Since this immune cell compartment plays a decisive role in the defense of the human immune system against S. aureus, we asked whether next-generation humanized mice, like NSG-SGM3 (NOD-scid IL2Rgnull-3/GM/SF) with improved myeloid reconstitution, would prove to be more resistant to infection. To our surprise, we found the contrary when we infected humanized NSG-SGM3 (huSGM3) mice with S. aureus: although they had stronger human immune cell engraftment than humanized NSG mice, particularly in the myeloid compartment, they displayed even more pronounced vulnerability to S. aureus infection. HuSGM3 mice had overall higher numbers of human T cells, B cells, neutrophils and monocytes in the blood and the spleen. This was accompanied by elevated levels of pro-inflammatory human cytokines in the blood of huSGM3 mice. We further identified that the impaired survival of huSGM3 mice was not linked to higher bacterial burden nor to differences in the murine immune cell repertoire. Conversely, we could demonstrate a correlation of the rate of humanization and the severity of infection. Collectively, this study suggests a detrimental effect of the human immune system in humanized mice upon encounter with S. aureus which might help to guide future therapy approaches and analysis of virulence mechanisms.